Outcome of a Food Observational Study Among Low-Income Preschool Children Participating in a Family-Style Meal Setting. (April 2015) - Treviño, Roberto P.; Vasquez, Liset; Shaw-Ridley, Mary; Mosley, Desiree; Jechow, Katherine; Piña, Christina
Introduction . In the United States, one out of every seven low-income children between the ages of 2 and 5 years is at risk for overweight and obesity. Formative research was conducted to determine if preschool children participating in family-style meals consumed the minimum food servings according to U.S. Department of Agriculture dietary guidelines. Method . Participants were 135 low-income children aged 3 to 4 years who attended an urban child care center. Participant's parents completed a Family Demographic Questionnaire to provide information on race/ethnicity, parent's level of education, and household income. Direct observation of children's food and beverage consumption during school breakfast and lunch was collected over 3 consecutive days. Dietary data were assessed using the Nutrition Data System for Research software. Height and weight measurements were obtained to determine risk for obesity. Descriptive statistics were reported by using the Statistical Package for the Social Sciences Version 16. Results . Among 135 participants, 98% identified as Mexican American, 75% lived at or below poverty level, and 24% reported a family history of diabetes. Children consumed less than half of the calories provided between breakfast and lunch and did not consume the minimum recommended dietary food servings. Despite the poor dietary intake, physical measurement findings showed 25% obesity prevalence among study participants. Conclusions . Findings support the need for evidenced-based early childhood obesity prevention programs that provide behavior change opportunities for children, their families, teachers, and menu planners. Family-style meal settings are ideal opportunities for implementing nutrition education strategies to prevent early childhood obesity.